IMPLEMENTASI PENDIDIKAN AKHLAK DI SEKOLAH DASAR ISLAM TERPADU (SDIT) AL-BADR KECAMATAN BANGKINANG KABUPATEN KAMPAR - Nelly Yusra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
We often hear a saying mentions that teaching children at the early stage of their life, it will be like you are writing on a stone. But if you teach someone during his adulthood, it will be such you are writing on water which traces nowhere. This proverb cannot be denied since character and moral are nurtured best in the earlier stage of children’s life. Early age of childhood is critical period for forming children character. Educational experts say that the failure in giving moral education in earlier stages of children life will cause bad problems at their adult life later. It becomes worst if they grow in a bad environment